Analysis Of Accuracy In Determining Diagnosis Coding And Completeness Of Claim Files For Pending Claims Bpjs Kesehatan Inpatient Services Uobk Simpang Lima Gumul Rsud Kediri District - Finda Sri Wahyuni; Amarin Yudhana; Wening Palupi Dewi (Journal of Hospital Management and Services, 2024)
Background. BPJS claims are the submission of all BPJS patient care costs by the Hospital to BPJS Health, carried out collectively and billed to BPJS Health every month through a verification process. Inaccuracy in determining diagnostic coding and incomplete claims files are the main problems in pending BPJS Health claims, which can cause losses for hospitals. The aim of the research is to analyze the accuracy in determining diagnostic coding and completeness of claim files for pending BPJS health claims for UOBK inpatient services at Simpang Lima Gumul (SLG) Hospital, Kediri Regency. Research methods. Analytical descriptive quantitative research, using observation data collection of 261 respondents using the Simple Random Sampling Technique method and analyzed using a Logistic Regression test. Research result. The majority had accuracy in diagnostic coding of 223 data (85.4%), the majority had completeness in the BPJS Health Claim File of 242 data (92.7%) and the majority had data that was not pending at 205 (78%). This is also supported by a significance value of p value ≤ 0.001, which means there is a significant influence between accuracy and completeness on pending BPJS Health claims. Conclusion. When the documents are incorrect and incomplete, BPJS Health claims will definitely be pending, so all officers need to be careful in anticipating pending claims.